Studi Eksplorasi Religiusitas Dan Implementasi Asuhan Keperawatan Spiritual Muslim (AKSM) Pada Mahasiswa Profesi Ners PSIK FKM UMI Makassar Tahun 2018 - Samsualam, Samsualam; Hidayat, Rahmat; Aswan, Karyanti Lestari (Window of Health : Jurnal Kesehatan, 2018)
Religiosity can describe a person's behavior at work, especially working as a health worker to help the healing process both physically, psychologically and spiritually. The purpose of this study was to analyze the level of religious religiosity of professional students and to analyze the implementation of Muslim spiritual nursing care for ners profession students in PSIK FKM Universitas Muslim Indonesia. This research method used quantitative and qualitative methods (Mix Method). Based on the results of the descriptive bivariate analysis of religiosity and the implementation of Muslim nursing care in 2018, it was shown that out of 0 (100%) respondents at a high level of religiosity overall did not implement complete Muslim spiritual nursing care, 24 people (100%) and 6 (100 %) respondents with a low level of religions overall did not carry out complete implementation of Muslim spiritual nursing care, namely 6 (100%) respondents. This shows that descriptively students who have high religiosity and low religiosity do not implement Muslim spiritual nursing care (AKSM).